Polyhydroxyalkanoates production from fermented domestic wastewater using phototrophic mixed cultures. (1st June 2021) - Almeida, J.R.; Serrano, E.; Fernandez, M.; Fradinho, J.C.; Oehmen, A.; Reis, M.A.M.
Highlights: PHA production with phototrophic mixed cultures was tested using real feedstocks. Two feeding strategies were evaluated: permanent feast (PF) and feast and famine (FF). PF strategy coupled to phosphate cycling or transient OLR improved PHA accumulation. Highest PHA productivities were attained under FF conditions with multi-pulse feeding. PHA accumulation of 30.8% PHA/VSS content attained under outdoor-simulated conditions. Abstract: Phototrophic mixed cultures (PMC) have been found to be a promising technology to produce polyhydroxyalkanoates (PHA), however, work performed thus far has focussed mainly on the use of synthetic feedstocks and operational conditions that differ from those expectable in full-scale processes. The goals of this work were to study, for the first time, the capability of PMCs to produce PHA using real fermented domestic wastewater as feedstock under mixing/light/temperature conditions that are naturally found in outdoor open systems. Various operational strategies were evaluated in this study to increase PHA productivity, namely the poly(3-hydroxybutyric-co-3-hydroxyvaleric) copolymer (PHBV) by PMC systems. Two lab-scale photobioreactors were operated in parallel, with transient illumination (12 h light/12 h dark) and subjected to feedstock fluctuations under two culture selection strategies that best suit the oxidative conditions of high rate algal ponds (HRAPs) which are commonly applied in wastewater treatment plants (WWTP). Under a permanent carbon feast regime (selection strategy 1), the PMC became highly enriched in phototrophic purple bacteria (PPB), and two complementary conditions that can improve the selection of PHA accumulating bacteria were discovered: phosphate cycling, where 20% PHA/VSS (86HB:14HV in a C-mol basis) with a light phase productivity of 0.23 g PHA/Ld_light phase was attained; and transitioning from selection under low organic loading rate (OLR) to high OLR where 17.6% PHA/VSS (60HB:40HV in C base) with a light phase productivity of 0.18 g PHA/Ld_light phase was achieved. Under a feast and famine regime (selection strategy 2), a PMC consortium of microalgae and PPB was obtained, and a multiple pulse feeding strategy during the first hours of the light phase in the selector reactor led to a 26.1% PHA/VSS (36HB:64HV in C base) content, with a productivity of 0.26 g PHA/Ld_light phase and 0.52 g PHA/Ld_feast phase. An accumulation test under higher light intensity led to 30.8% PHA/VSS (85HB:15HV on a C-mol basis) with a productivity of 2.67 g PHA/Ld, along the 8 h of accumulation.